1985
DOI: 10.1038/clpt.1985.83
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tobacco and non-tobacco cigarette smoking on endothelium and platelets

Abstract: Endothelial damage and platelet activation may mediate increased cardiovascular morbidity and mortality in tobacco cigarette smokers. Our study was designed to determine whether acute effects of tobacco smoking on endothelium and platelets could be avoided by the substitution of non-tobacco cigarettes. Twenty healthy nonsmokers smoked two tobacco cigarettes in 20 minutes and on another occasion (separated by 1 week) smoked two cigarettes made from wheat, cocoa, and citrus plants. Mean endothelial cell counts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(52 citation statements)
references
References 0 publications
4
48
0
Order By: Relevance
“…This is supported with the finding that, in the presence of L-NNA, there was no significant difference between the control and nicotine-treated uterine arteries. Previous studies have indicated that chronic cigarette smoking causes morphologic changes and functional alteration in endothelial cells (Davis et al, 1985;Powell, 1998). In addition, inhibition of eNOS with N G -monomethyl-L-arginine produced a significantly greater decrement in forearm blood flow in smokers versus nonsmokers (McVeigh et al, 1996), suggesting that cigarette smoking altered endothelial function and increased vascular tone.…”
Section: Discussionmentioning
confidence: 88%
“…This is supported with the finding that, in the presence of L-NNA, there was no significant difference between the control and nicotine-treated uterine arteries. Previous studies have indicated that chronic cigarette smoking causes morphologic changes and functional alteration in endothelial cells (Davis et al, 1985;Powell, 1998). In addition, inhibition of eNOS with N G -monomethyl-L-arginine produced a significantly greater decrement in forearm blood flow in smokers versus nonsmokers (McVeigh et al, 1996), suggesting that cigarette smoking altered endothelial function and increased vascular tone.…”
Section: Discussionmentioning
confidence: 88%
“…Smoking is associated with a direct toxic effect on human endothelial cells, reduces endothelial prostacyclin production and increases leukocyte adhesion to endothelial cells. [24][25][26][27] Cigarette smoke contains a large number of oxidants; the role of oxygen-derived free radicals in mediating endothelial dysfunction can be modulated by the potent antioxidant vitamin C. [28][29][30] Alternatively, smoking increases endothelial angiotensin II production, which reduces nitric oxide activity, and might contribute to endothelial damage in smokers. 31 Increased platelet and serum fibrinogen, as well as decreased serum plasminogen levels known to occur in smokers, might also impair endothelial function in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kritz and Sinzinger (30) observed an increase in markers of platelet activation and a decrease in platelet sensitivity to PGI2 among 12 nonsmokers exposed for 20-min in an 18 m3 room in which 30 Gitanes had recently been smoked. The hypercoagulable state demonstrated among nonsmokers acutely exposed to ETS (30)(31)(32)(33)(34) resembles the acute changes in smokers who consume one or two cigarettes after a period of abstinence (35)(36)(37)(38)(39)(40)(41)(42)(43). Schmid et al (31) found that, prior to ETS exposure, the platelets of nonsmokers were significantly less activated than those of smokers, whereas after 20 min exposure to ETS, platelet activation increased among the nonsmokers exposed to ETS (p < 0.01) but remained constant among the active smokers (p > 0.05).…”
Section: Experimental Studies Ofets Exposurementioning
confidence: 99%